2021
DOI: 10.1097/cm9.0000000000001402
|View full text |Cite
|
Sign up to set email alerts
|

A risk score system for stratifying the risk of relapse in B cell acute lymphocytic leukemia patients after allogenic stem cell transplantation

Abstract: Background For patients with B cell acute lymphocytic leukemia (B-ALL) who underwent allogeneic stem cell transplantation (allo-SCT), many variables have been demonstrated to be associated with leukemia relapse. In this study, we attempted to establish a risk score system to predict transplant outcomes more precisely in patients with B-ALL after allo-SCT. Methods A total of 477 patients with B-ALL who underwent allo-SCT at Peking University People's Hospital from Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In a recent study including 477 B-ALL patients who underwent allo-HSCT, Cao et al [19] demonstrated that post-HSCT MRD, but not pre-HSCT MRD was associated with higher CIR and shorter survival after multivariate analysis. In contrast to the result by Cao et al [19] , we found that both pre-and post-MRD could be used for discriminating patients into different relapse risk groups for T-ALL patients, although post-HSCT MRD was better than pre-HSCT MRD in predicting leukemia relapse (table 2 and fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study including 477 B-ALL patients who underwent allo-HSCT, Cao et al [19] demonstrated that post-HSCT MRD, but not pre-HSCT MRD was associated with higher CIR and shorter survival after multivariate analysis. In contrast to the result by Cao et al [19] , we found that both pre-and post-MRD could be used for discriminating patients into different relapse risk groups for T-ALL patients, although post-HSCT MRD was better than pre-HSCT MRD in predicting leukemia relapse (table 2 and fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…There was higher percentage of cases in the positive pre-HSCT MRD group receiving haploidentical HSCT than in the negative pre-HSCT group (P=0.014). However, our previous studies demonstrated that, for ALL patients or acute myeloid leukemia patients, haploidentical HSCT had a superior anti-leukemia activity to MSDT [15,17,19,35] . Higher percentages of patients in the positive MRD groups received IFN-γ or DLI for relapse intervention than those of the negative MRD groups either pre-or post-HSCT (P=0.030 or <0.001, respectively) (table 1).…”
Section: Patient Characteristics and Transplant Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…For now, there are many ways to treat leukemia clinically, but because of drug resistance or relapse, leukemia patients still need more treatment strategies. [15][16][17][18] A number of experiments and epidemiological studies have shown that iron metabolism disorders are related to the occurrence and development of AL. [19][20][21] The occurrence of leukemia involves many genes related to iron metabolism, including hemochromatosis (HFE) gene, transferrin receptor 1 gene, and other genes involved in iron metabolism.…”
Section: Introductionmentioning
confidence: 99%